Pengaruh Variasi Konsentrasi Bahan Pengikat Terhadap Formulasi dan Stabilitas Fisik Tablet Detergen Effervescent Ekstrak Daun Serai Dapur (Cymbopogon citratus) - Girsang, Valentina; Kusuma Dewi, Liestyani; Rustaman, Heri; Sa’adah, Anifatus; Wibowo, Anisa Devi Kharisma (Jurnal Farmasi & Sains Indonesia, 2024)
Lemongrass leaves (Cymbopogon citratus) contain saponins that can form foam in water so that they are used as natural compounds that produce foam used in industry. The purpose of this study was to provide the effect of variations in PVP concentrations of 2%, 3% and 4% on the physical characteristics, physical stability and detergenation ability of effervescent detergent tablets of lemongrass leaf extract (Cymbopogon citratus). This study used the maceration extraction method with 96% ethanol and the manufacture of effervescent tablets by the wet granulation method. The results of the characterization and stability study of effervescent tablets of lemongrass leaf extract with variations in PVP concentration showed that the tablets met the requirements for characterization testing of effervescent tablets before and after stability. Based on the results of the foam height test on effervescent tablets before and after stability did not affect the high foam with the results of F1, F2, F3 after stability of 86.56 ± 0.34; 86.56 ± 0.34; 88.20 ± 2.28. This study shows that PVP affects the characteristics and stability of tablets but does not affect the detergent ability of effervescent detergent tablets.